INTERACTION OF VISUAL ARTS LEARNING IN A VIRTUAL COMMUNITY - Nugrahani, Rahina; Rahmaningtyas, Hasti; Wibawanto, Wandah; Widagdo, Pratama Bayu (PEOPLE: International Journal of Social Sciences, 2020)
In cyberlearning, interaction becomes one of the features that determine learning success. This study underlines the interaction of visual arts learning in the virtual community. Virtual community facilitates informal art learning in cyberspace as they have comprehensive capacity related to the strategy of organizing cyber-based learning. This study involved 24 informants consisting of founders, members, and learning instructors of a virtual community in Indonesia. Using virtual ethnography as a research method, this study found three patterns of learning interactions in the virtual community, that are the interaction of learning participants with learning content; learning participant interaction with the instructor; and interaction between learning participants. Through these three interaction patterns, cyber-based art learning can be formulated in a virtual community.